PENGARUH PENDIDIKAN KEWIRAUSAHAAN DI LINGKUNGAN KELUARGA, PEMBELAJARAN KEWIRAUSAHAAN DI SEKOLAH, SERTA ACHIEVEMENT MOTIVE TERHADAP MINAT KEWIRAUSAHAAN SISWA SMA - Eny Eko Sulistyowati; Sugeng Hadi Utomo; Bambang Sugeng (Pascasarjana Universitas Negeri Malang, 2016)
The study aims to determine the influence of family environment in entrepreneurship education, entrepreneurship learning in school, as well as the achievement motive against the interest of entrepreneurship of senior high school students throughout Malang. The study uses a quantitative approach. The study population was high school state students throughout Malang. The process of sampling using proportional random sampling technique, resulting in a sample of 347 high school students. Data were analyzed using analysis of quantitative description. The findings show that: (1) the family environment of entrepreneurship education in entrepreneurship affect the interest of students, (2) entrepreneurial learning in schools using learning media has an influence on students 'interest in entrepreneurship, (3) Achievement motive significant effect on students' interest in entrepreneurship. Based on the findings, it can be suggested (1) to the parents to continue to teach children as early as possible to have the properties of an entrepreneur as well as supporting the child when choosing to become entrepreneurs rather than being an employee, (2) to the school, is expected in perform entrepreneurial learning, can follow changes in the business world, using a variety of learning media and increase students' motivation to try to become entrepreneurs by using media appropriate learning in school. Penelitian ini bertujuan guna mengetahui pengaruh pendidikan kewirausahaan  di lingkungan keluarga, pembelajaran kewirausahaan di sekolah, serta achievement motive terhadap minat kewirausahaan siswa SMA Negeri se-Kabupaten Malang. Penelitian ini menggunakan pendekatan kuantitatif. Populasi penelitian adalah siswa Sekolah Menengah Atas Negeri se-Kabupaten Malang. Proses penarikan sampel menggunakan teknik proportional random sampling, sehingga menghasilkan sampel sejumlah 347 siswa SMA. Teknik analisis data menggunakan analisis deskripsi kuantitatif. Temuan penelitian menunjukkan bahwa (1) pendidikan kewirausahaan di lingkungan keluarga berpengaruh terhadap minat kewirausahaan siswa, (2) pembelajaran kewirausahaan disekolah dengan menggunakan media pembelajaran memiliki pengaruh terhadap minat kewirausahaan siswa, (3) achievement motive berpengaruh signifikan terhadap minat kewirausahaan siswa. Berdasarkan pada temuan penelitian tersebut, dapat disarankan (1) kepada orangtua siswa untuk terus mengajarkan anak-anak sedini mungkin untuk memiliki sifat-sifat seorang wirausaha serta mendukung anak ketika memilih menjadi wirausaha daripada menjadi pegawai, (2) kepada pihak sekolah, diharapkan dalam melakukan pembelajaran kewirausahaan, dapat mengikuti perubahan pada dunia usaha, menggunakan media belajar yang bervariasi dan meningkatkan motivasi siswa untuk mencoba menjadi wirausaha dengan menggunakan media pembelajaran yang tepat di sekolah.